Factors Influencing Stock Price Underpricing During IPOs on the Indonesia Stock Exchange(Empirical Study on Companies Listed on IDX from 2019 to 2023) - Sella Septianita; Muslimin (Teewan Journal Solutions, 2025)
The phenomenon of underpricing is characterized by a significant increase in stock prices in the secondary market compared to their initial offering prices. This reflects the presence of information asymmetry and market uncertainty regarding the true value of newly listed companies. Underpricing can lead to potential losses for issuing firms while offering early investors the opportunity to gain initial returns. This study aims to examine the influence of profitability, leverage, firm size, and underwriter reputation on underpricing. The research focuses on companies that conducted an Initial Public Offering (IPO) on the Indonesia Stock Exchange during the 2019–2023 period. From a population of 297 companies, a purposive sampling technique was applied based on specific criteria, resulting in a sample of 202 companies. The study employs secondary data and applies multiple linear regression analysis, grounded in signaling theory. The findings reveal that profitability, leverage, firm size, and underwriter reputation collectively have a significant effect on underpricing. Partially, profitability has a significant negative effect on underpricing, while leverage shows a significant positive effect. In contrast, firm size and underwriter reputation do not have a significant impact on underpricing. These results suggest that investors place greater emphasis on financial performance indicators such as profitability and leverage when deciding to invest in IPO firms, as they believe that companies with strong financial performance will yield favorable returns in the future, prompting them to pay a premium for such stocks.